Development and Implementation of Instructional Video Dubbing (IVD) in Assessing Intelligibility - Ateng Kurnia; Rudi Hartono; Mursid Saleh; Sri Wahyuni (Universitas Negeri Semarang, 2022)
The study aims to assess the feasibility of the development and implementation of instructional video dubbing (IVD). It is a dynamic assessment technique for teaching intelligible pronunciation. The assessment is based on Vygotsky's zone of proximal development and mediated learning concept. A narrative case study was used, and the procedure steps up using analyzing, tailoring, and modeling (ATM) portrayed the learning atmosphere with a pre-test, mediated learning, and a post-test. The data were garnered from two fairs of peer in depth-interviewed as purposive random samples of sixty undergraduate 3rd-year student-teachers in the English education program who participated with consent. Cause of their being non-native pre-service English teachers whose utterances will become models for their students. The case study involved three participants in purposive samples. They need mediation to internalize the concepts of intelligible pronunciation. Therefore, the practice of IVD has a duty to provide learners with teachers’ scaffolding and feedback as well as peer-to-peer mediation. It also becomes a laboratory for reflective practice, particularly improving student-teacher intelligibility, and early teachers’ professional development in general. The finding reveals that the practice of IVD as a dynamic assessment, in my research context, brings about three aspects of intelligible pronunciation that are recommended to be internalized, namely syllable stress, unstressed syllable, and schwa as corrective feedback that can be used for a milestone of improving individual learning potential and their teacher identities, agency and professional development corresponding to the need of student-teachers current and future achievement.